2018
DOI: 10.1016/j.scienta.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Cluster illumination differentially affects growth of fruits along their ontogeny in highbush blueberry ( Vaccinium corymbosum L.)

Abstract: A B S T R A C TShading highbush blueberry plants generally leads to a delayed fruit development. Experiments have been performed to study the effects of light on fruit growth independently from the rest of the canopy. Clusters were shaded during different fruit growth periods. The equatorial diameter of the fruits as a function of days after full bloom followed a double-sigmoidal growth pattern, being fitted using a Gompertz II nonlinear mixed model, and absolute growth rates were obtained from each fitted mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…However, the results of this study showed that after continuous girdling for many years, the quality of jujube fruit not only did not improve, but also decreased to a certain extent. The test results showed that the weight, hardness and geometric-mean diameter of jujube fruit from non-girdled jujube trees were significantly greater than the corresponding index value of girdled jujube trees, which was quite different from the general conclusions, such as that girdling can increase the weight of a single fruit, and so on [28,29]. What is more, the observation results of microscope and scanning-electron-microscope images showed that there were a large number of big porous structures in the pulp of the girdled jujube fruit compared with the non-girdled jujube fruit.…”
Section: Effects Of Long-term Girdling Of Jujube Trees On Jujube-frui...mentioning
confidence: 62%
“…However, the results of this study showed that after continuous girdling for many years, the quality of jujube fruit not only did not improve, but also decreased to a certain extent. The test results showed that the weight, hardness and geometric-mean diameter of jujube fruit from non-girdled jujube trees were significantly greater than the corresponding index value of girdled jujube trees, which was quite different from the general conclusions, such as that girdling can increase the weight of a single fruit, and so on [28,29]. What is more, the observation results of microscope and scanning-electron-microscope images showed that there were a large number of big porous structures in the pulp of the girdled jujube fruit compared with the non-girdled jujube fruit.…”
Section: Effects Of Long-term Girdling Of Jujube Trees On Jujube-frui...mentioning
confidence: 62%
“…In addition, this study showed that ABC transporters, pyrimidine metabolism, and purine metabolism pathways were common in the three comparison groups, indicating that these three metabolic pathways of blueberry fruits are vulnerable to shading treatment, which led to the differences in DAMs in these pathways, thus suggesting that they may have an important impact on fruit quality. Several studies have shown that shading of blueberry plants usually leads to delayed fruit development ( Godoy et al, 2018 ) and may be considered a promising tool to delay harvest for commercial purposes ( Beraud & Ulloa, 2015 ). Blueberries, as shrubby plants, can readily be shaded for agricultural purposes, and Kim et al (2011) showed that to achieve the best photosynthesis and blueberry growth, we must avoid shading levels exceeding 60 % of the full light level.…”
Section: Discussionmentioning
confidence: 99%